Ambient temperature effects on stress-induced hyperthermia in Svalbard ptarmigan - Nord, Andreas; Folkow, Lars (Biology Open, 2019)
Stress-induced hyperthermia (SIH) is commonly observed during handling in homeotherms. However, in birds, handling in cold environments typically elicits hypothermia. It is unclear whether this indicates that SIH is differently regulated in this taxon or if it is due to size, because body temperature changes during handling in low temperatures have only been measured in small birds <0.03 kg (that are more likely to suffer high heat loss when handled). We have therefore studied thermal responses to handling stress in the intermediate-sized (0.5–1.0 kg) Svalbard ptarmigan ( Lagopus muta hyperborea ) in 0°C and −20°C, in winter and spring. Handling caused elevated core body temperature and peripheral vasoconstriction that reduced back skin temperature. Core temperature increased less, and back skin temperature decreased more, in −20°C than in 0°C, probably because of higher heat-loss rate at the lower temperature. Responses were qualitatively consistent between seasons, despite higher body condition/insulation in winter and dramatic seasonal changes in photoperiod, both of which could possibly affect stress responsiveness. Our study supports the notion that SIH is a general thermoregulatory reaction to acute stressors in endotherms, but also suggests that body size and thermal environment should be taken into account when evaluating this response in birds.